Epistemic Agency as a Mediator in Dual-Path Learning: Insights from Indonesian Chemistry Classrooms - Ramona Nintias R. Abas; Weny J.A. Musa; Lukman Abdul Rauf Laliyo; Masrid Pikoli; Akram La Kilo (Universitas Negeri Gorontalo, 2026)
This study investigates the mediating role of epistemic agency in the relationship between students’ perceptions of constructivist learning environments and their conceptual understanding in Indonesian chemistry classrooms. A sequential explanatory mixed-methods design was employed, integrating quantitative and qualitative approaches. In the quantitative phase, data were collected from 712 high school students across five schools using an adapted Constructivist Learning Environment Survey (CLES) and a three-tier diagnostic chemistry test. Rasch modeling confirmed the strong psychometric properties of the adapted CLES, while structural equation modeling (SEM) revealed that epistemic agency significantly mediated the relationship between classroom environment perceptions and conceptual understanding. In the qualitative phase, thematic analysis of interviews with 12 selected students uncovered three dominant themes contributing to misconceptions: limited dialogic space, lack of contextualization, and teacher-dominated instruction. The integration of both data strands demonstrates that epistemic agency is not only influenced by pedagogical practices but also shaped by cultural norms. These findings extend the dual-path learning framework by embedding agency as a key mechanism for conceptual change. Pedagogically, the results underscore the need for dialogic, student-centered learning environments that promote active participation and reduce misconceptions. Policy-wise, the findings align with the OECD Learning Compass 2030 and Indonesia’s Merdeka Belajar curriculum, emphasizing the importance of agency-oriented strategies in achieving global education standards.